2014
DOI: 10.1063/1.4862745
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the photocurrent and photoluminescence of single crystal monolayer MoS2 with resonant plasmonic nanoshells

Abstract: Monolayer molybdenum disulfide (MoS 2) produced by controlled vapor-phase synthesis is a commercially promising new two-dimensional material for optoelectronics because of its direct bandgap and broad absorption in the visible and ultraviolet regimes. By tuning plasmonic core-shell nanoparticles to the direct bandgap of monolayer MoS 2 and depositing them sparsely (<1% coverage) onto the material's surface, we observe a threefold increase in photocurrent and a doubling of photoluminescence signal for both exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(225 citation statements)
references
References 32 publications
3
220
1
1
Order By: Relevance
“…For instance, hot electrons can change the doping of graphene [140] or molybdenum disulfide (MoS 2 ) [42,143], leading to structural phase transitions [42] or modulation of the absorption spectrum [143]. Hot electrons can also be used for enhancing MoS 2 photocatalysis of hydrogen evolution [144] and the photoluminescence of MoS 2 [141]. A photodetector based on hot electron injection into graphene has also been reported [139] ( Figure 5A).…”
Section: Hot Electrons With 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, hot electrons can change the doping of graphene [140] or molybdenum disulfide (MoS 2 ) [42,143], leading to structural phase transitions [42] or modulation of the absorption spectrum [143]. Hot electrons can also be used for enhancing MoS 2 photocatalysis of hydrogen evolution [144] and the photoluminescence of MoS 2 [141]. A photodetector based on hot electron injection into graphene has also been reported [139] ( Figure 5A).…”
Section: Hot Electrons With 2d Materialsmentioning
confidence: 99%
“…On the contrary, plasmonics enable strong light-matter interaction with 2D materials due to high field concentration [135][136][137][138]. Additionally, it has been shown that surface plasmons in metallic nanoparticles can directly interact with 2D materials through hot electron injection [42,[139][140][141][142][143]. For instance, hot electrons can change the doping of graphene [140] or molybdenum disulfide (MoS 2 ) [42,143], leading to structural phase transitions [42] or modulation of the absorption spectrum [143].…”
Section: Hot Electrons With 2d Materialsmentioning
confidence: 99%
“…Several strategies have been proposed and preliminary demonstrations have been reported including use of plasmonic metal particles, shells or resonators to enhance photocurrent and photoluminescence. [27][28][29][30][31][32][33][34][35][36][37] More sophisticated and lossless dielectric optical cavities such as photonic crystals and ring resonators have also been used to enhance absorption, mainly aimed at emission applications in monolayer samples. [38][39][40][41] For large area photovoltaic applications, light trapping strategies that involve little or no micro-or nanofabrication and patterning are desirable to improve performance while minimizing cost.…”
Section: Absorption and Photonic Designmentioning
confidence: 99%
“…Placing metallic objects by an ordered array with dimension and pitch in the order of the excitation wavelength is a classic way to form plasmonic nanostructures. Either stacking 2D materials on top of those plasmonic nanostructures, or patterning plasmonic nanostructures on top of 2D materials can increase the light absorption at certain wavelengths [93][94][95][96][97]. A significant enhancement~65% of photoluminescence intensity are reported for a monolayer MoS 2 -coated gold nanoantennas system [98].…”
Section: Photodetectormentioning
confidence: 97%
“…First, the introduction of photonic structures into 2D materials can significantly enhance their photoresponsivity [93][94][95][96][97][98][99][100][101][102][103][104][105][106]. On the other hand, by electrostatically tuning the Fermi level of 2D materials, with which photonic structures like waveguides, resonators and cavities are integrated, their modulation performance can be improved [107][108][109][110][111][112][113].…”
Section: Photonic Structure-integrated 2d Materials Optoelectronicsmentioning
confidence: 99%